Current developments in Lumban's embroidery industry - Faronilo, Maria Asuncion Guadalupe O.; Rayala, Maria Monica E. (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT Embroidery is part of Filipino culture. It is a craft which has once been associated only to women, and a living that earns for a family. To the residents of Lumban, Laguna, embroidery is also their "way of life" (Dhamjia, 2004, p.17). Inspired by two research studies made by Panganiban (1993) and Tañeza (2003), this research reviewed the present conditions of the embroidery industry of Lumban, Laguna. This case study described the profile of embroidery entrepreneurs and workers, documented embroidery stitches used by selected embroiderers, determined new developments and changes, traced the developments and changes from the two past studies,identified current issues and concerns. The research was limited by the information from interviews by the number of randomly selected respondents composed of embroidery workers, embroidery business owners, and other people indirectly involved in the production of embroidery. This research enriched the information about the long surviving craft of Burdang Lumban. The usage of technology in production and communication, changes and common frequencies in systems of embroidery trade, documentation of embroidery stitches and motifs from selected embroiderers, utilization of new material, and progress in support and promotion of the industry were determined on the course of the study. Present concerns and issues include finance, price regulation, future embroiderers, market, crab mentality, use of Lumban's identity by other embroidery producers, and variety of products were given with recommendations as suggestions for probable solutions.
Thesis (BSCT)--University of the Philippines Diliman.
Keywords: Embroidery industry -- Philippines -- Lumban, Quezon